Organoid technology and applications in lung diseases: Models, mechanism research and therapy opportunities - Chen, Jingyao; Na, Feifei (Frontiers in Bioengineering and Biotechnology, 2022)
The prevalency of lung disease has increased worldwide, especially in the aging population. It is essential to develop novel disease models, that are superior to traditional models. Organoids are three-dimensional (3D) in vitro structures that produce from self-organizing and differentiating stem cells, including pluripotent stem cells (PSCs) or adult stem cells (ASCs). They can recapitulate the in vivo cellular heterogeneity, genetic characteristics, structure, and functionality of original tissues. Drug responses of patient-derived organoids (PDOs) are consistent with that of patients, and show correlations with genetic alterations. Thus, organoids have proven to be valuable in studying the biology of disease, testing preclinical drugs and developing novel therapies. In recent years, organoids have been successfully applied in studies of a variety of lung diseases, such as lung cancer, influenza, cystic fibrosis, idiopathic pulmonary fibrosis, and the recent severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic. In this review, we provide an update on the generation of organoid models for these diseases and their applications in basic and translational research, highlighting these signs of progress in pathogenesis study, drug screening, personalized medicine and immunotherapy. We also discuss the current limitations and future perspectives in organoid models of lung diseases.